Trauma intergeracional da escravidão: experiência emocional de mães afrodescendentes que perderam seus filhos pela ação violenta do Estado - Souza, Lourdes Alves de (2023)
The trauma from slavery and the generational transmission of its psychosocial, political, economic, cultural, and educational consequences are legacies of contemporary society. In this context, this study aimed to identify and reflect on the narratives of Afro-descendant women about the violent loss of children killed by the action of the State and its relationship with the intergenerational trauma of slavery. Specifically, it sought to understand whether and how historical aspects related to the intergenerational trauma of slavery impact the life and emotional health of Afrodescendant women, as well as the quality of the emotional experience of bereaved mothers resulting from the violent loss of their children. For that, qualitative exploratory research was carried out through life history interviews. Fifteen Afro-descendant women participated who had one or more children killed by the action of the State. The information was analyzed by thematic categories deduced from the set of interviews. The results showed the presence of intergenerational processes in the experience of mourning and in the psychosocial life of the participating black mothers. They also pointed out that the violent death of their children adds to various situations of violence and abandonment that pervade the lives of the narrators, as well as their ancestors. It is proposed that the traumas experienced by black women need to be recognized and integrated into individual and collective consciousness to enable the healing of historical wounds that are repeated daily in situations of extreme violence and dehumanization of black people. This study is extremely relevant for the scientific and social field, as it brings to light a theme that remains invisible in different contexts, but alive in the psychic history of the Brazilian people